Calculation of Morse Potential for Diamond Crystals. Applification to AnhaiTnonic Effective Potential - Hung, Nguyen Van; Toan, Nguyen Cong; Trung, Nguyen Bao; Giang, Ngo Hoang (VNU Journal of Science: Mathematics - Physics; Vol 24 No 3, 2008)
Abstract